Resisting government rendered surveillance in a local authority. Issue 8 (3rd August 2019) - Kayas, Oliver G.; Hines, Tony; McLean, Rachel; Wright, Gillian H.
ABSTRACT: The paper illustrates and discusses how the performance management systems in a UK local authority are transformed into a surveillance system. A case study analysis reveals that the surveillance is engendered by central government and enacted by senior managers who conform to policies demanding the introduction of strict performance management systems that dehumanize work processes because employees are deemed untrustworthy. The paper shows that employees resist this government rendered surveillance because they believe it undermines their interests as well as the interests of the public by damaging the quality of the services delivered.